2021
DOI: 10.1136/gutjnl-2021-326023
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of a microbial toxin from the gut microbiome to mesencephalic mitochondria

Abstract: ObjectiveIdiopathic Parkinson’s disease (PD) is characterised by alpha-synuclein (aSyn) aggregation and death of dopaminergic neurons in the midbrain. Recent evidence posits that PD may initiate in the gut by microbes or their toxins that promote chronic gut inflammation that will ultimately impact the brain. In this work, we sought to demonstrate that the effects of the microbial toxin β-N-methylamino-L-alanine (BMAA) in the gut may trigger some PD cases, which is especially worrying as this toxin is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 84 publications
2
39
0
Order By: Relevance
“…Although this field is vast, one area of interest involves the naturally occurring bacterial toxin ß-N-methylamino-L-alanine (BMAA). Occasionally found in dangerously toxic concentrations within certain seafood, BMAA consumption has been shown to cause a significant shift in the microbial environment of the gut [ 122 , 123 ], demonstrating to have profound effects on the propagation of αSyn from the gut to the brain and the subsequent development of PD [ 122 , 124 ]. Interestingly, BMAA has causal links to both ALS and PD, being the key contributor to the rare incidence of the ALS-PD complex in the western Pacific islands of Guam and Japan [ 125 , 126 ].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Although this field is vast, one area of interest involves the naturally occurring bacterial toxin ß-N-methylamino-L-alanine (BMAA). Occasionally found in dangerously toxic concentrations within certain seafood, BMAA consumption has been shown to cause a significant shift in the microbial environment of the gut [ 122 , 123 ], demonstrating to have profound effects on the propagation of αSyn from the gut to the brain and the subsequent development of PD [ 122 , 124 ]. Interestingly, BMAA has causal links to both ALS and PD, being the key contributor to the rare incidence of the ALS-PD complex in the western Pacific islands of Guam and Japan [ 125 , 126 ].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Most importantly, a recent report from our group demonstrated that BMAA oral administration in WT mice increased intestinal inflammation, loss of intestinal barrier integrity and caudo-rostral progression of ASYN. Furthermore, we observed that BMAA induced mitochondrial dysfunction leading to neuroinflammation, dopaminergic neuronal loss, and motor deficits [ 176 ]. Considering the above, accumulating evidence suggests that some members of the gut microbiota may produce toxins targeting the mitochondria of the ENS and CNS that could result in subsequent neurodegeneration [ 139 ].…”
Section: Oxidative Stress and Chronic Inflammation Interdependence In...mentioning
confidence: 99%
“…In GUT, Esteves et al 9 used the bacterial toxin β-N-methylamino-L-alanine (BMAA), which is naturally produced by dinoflagellates and cyanobacteria and can accumulate to dangerous levels in seafood like mussels and oysters 10. BMAA was supplemented in the drinking water of mice to investigate whether a body or gut first type of PD could be elicited.…”
mentioning
confidence: 99%
“…Esteves et al 9 also touch on the vulnerability of different brain regions in their model. In line with what is known, they find mesencephalic neurons to be much more sensitive to the insult than neurons in other regions of the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation